2020
DOI: 10.29303/ipr.v3i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kualitas Minyak Goreng Berdasarkan Suhu Pemanasan Dengan Metode Koefisien Viskositas Falling Ball

Abstract: This study aims to determine the effect of temperature on oil viscosity or viscosity using the falling ball method. The approach in this study uses a quantitative approach to the type of laboratory experimental research. The population of this research is cooking oil, by taking three types of oil samples. The three types consisted of palm oil, coconut, and olive which were then observed for their effects on temperature using the fall ball method. Data were collected through laboratory experiments with measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The higher the temperature of the fluid, the less viscous the fluid is. In his research, K. Shoaliha [11] showed a decrease in the value of the viscosity coefficient in various heated cooking oils. The same study results were also shown by B. Esteban [12].…”
Section: Figure 1 Coconut Shell Active Charcoalmentioning
confidence: 96%
See 1 more Smart Citation
“…The higher the temperature of the fluid, the less viscous the fluid is. In his research, K. Shoaliha [11] showed a decrease in the value of the viscosity coefficient in various heated cooking oils. The same study results were also shown by B. Esteban [12].…”
Section: Figure 1 Coconut Shell Active Charcoalmentioning
confidence: 96%
“…Y. Eguchi, [13] used this method to determine the Rheological Property of Blood. E. Yusibani and K. Shoaliha [9,11] used it to determine the viscosity of various types of cooking oil. The principle of this method is to measure the time it takes the ball to fall through the fluid a certain distance.…”
Section: Figure 1 Coconut Shell Active Charcoalmentioning
confidence: 99%
“…The higher the viscosity, the greater the deep shear resistance (SYAFRIANI, 2019). This viscosity is calculated by measuring the flow time of a liquid whose amount is determined through the viscosimeter hole (Shoaliha, 2019).…”
Section: Viscositymentioning
confidence: 99%